Bimanual coupling effect during a proprioceptive stimulation - M. Biggio (Nature Portfolio, 2021)
Abstract Circle-line drawing paradigm is used to study bimanual coupling. In the standard paradigm, subjects are asked to draw circles with one hand and lines with the other hand; the influence of the concomitant tasks results in two “elliptical” figures. Here we tested whether proprioceptive information evoked by muscle vibration inducing a proprioceptive illusion (PI) of movement at central level, was able to affect the contralateral hand drawing circles or lines. A multisite 80 Hz-muscle vibration paradigm was used to induce the illusion of circle- and line-drawing on the right hand of 15 healthy participants. During muscle vibration, subjects had to draw a congruent or an incongruent figure with the left hand. The ovalization induced by PI was compared with Real and Motor Imagery conditions, which already have proved to induce bimanual coupling. We showed that the ovalization of a perceived circle over a line drawing during PI was comparable to that observed in Real and Motor Imagery condition. This finding indicates that PI can induce bimanual coupling, and proprioceptive information can influence the motor programs of the contralateral hand.